TRANSPARENCY AGAINST MISINFORMATION? Analysis of how Lupa and Aos Fatos agencies use public transparency mechanisms in verifying dubious content disseminated digitally - Nascimento, Thatiany; Lycarião, Diógenes; Nocrato, Suzete (Brazilian journalism research, 2024)
ABSTRACT – This paper analyzes how two fact-checking agencies, Lupa and Aos Fatos, utilized public transparency tools in verifying misinformation spread digitally in 2022. Through content analysis, 63 checks were identified using transparency tools, which represented less than 7% of the total checks conducted (950). However, such tools proved decisive for verifications involving subjects, agents, and public authorities. We discuss the implications of these results for the role played by fact-checking agencies in combating misinformation and their declared support for the defense of Brazilian democracy. RESUMO – Este trabalho analisa como duas agências de checagem, Lupa e Aos Fatos, utilizaram-se de ferramentas de transparência pública na verificação de desinformação difundida digitalmente em 2022. Por meio de análise de conteúdo, identificou-se 63 checagens com ferramentas de transparência, o que representou menos de 7% do total das checagens realizadas (950). Contudo, tais ferramentas se mostraram decisivas para as verificações envolvendo assuntos, agentes e autoridades públicas. Discutimos as implicações desses resultados para o papel ocupado pelas agências de checagem no enfrentamento à desinformação e no seu apoio declarado à defesa da democracia brasileira. RESUMEN – Este trabajo analiza cómo dos agencias de verificación, Lupa y Aos Fatos, utilizaron herramientas de transparencia pública en la verificación de desinformación difundida digitalmente en 2022. Mediante un análisis de contenido, se identificaron 63 verificaciones con herramientas de transparencia, lo que representó menos del 7% del total de las verificaciones realizadas (950). Sin embargo, tales herramientas se mostraron decisivas para las verificaciones involucrando asuntos, agentes y autoridades públicas. Discutimos las implicaciones de estos resultados para el papel desempeñado por las agencias de verificación en el enfrentamiento a la desinformación y en su apoyo declarado a la defensa de la democracia brasileña.